The guards - Bruen, Ken (Bruen, Ken. Jack Taylor novels., 2003)
Jack Taylor is a disgraced ex-cop in Galway. Mourning the death of his father, he is slowly drinking to oblivion. He has an ability to "find things" and is asked to investigate a teenage suicide. This leads him into a dangerous confrontation with a powerful businessman. A darker conspiracy slowly unfolds. Aided by a punk girl, he fumbles towards a lethal solution. The narrative is fueled by black humour, stark violence and moments of radiance. The Guards remain as a chorus in the background, never altogether past, infringing on Jack Taylor at the least expected moment. The intimate, bustling city of Galway, crashing into prosperity, illuminates the story at every turn.